2008
DOI: 10.1113/jphysiol.2008.161703
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐gated proton channels: what's next?

Abstract: This review is an attempt to identify and place in context some of the many questions about voltage-gated proton channels that remain unsolved. As the gene was identified only 2 years ago, the situation is very different than in fields where the gene has been known for decades. For the proton channel, most of the obvious and less obvious structure-function questions are still wide open. Remarkably, the proton channel protein strongly resembles the voltage-sensing domain of many voltage-gated ion channels, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 179 publications
4
59
1
1
Order By: Relevance
“…To know whether A206stop retains the properties of Hv channels, we assessed several hallmark properties of Hv channel currents, including proton permeation, zinc sensitivity, and pHdependent gating (26,27). We initially examined proton-exporting activity by measuring intracellular pH (pH in ) using a pH-sensitive ratiometric dye, BCECF, under whole-cell patch clamp.…”
Section: Resultsmentioning
confidence: 99%
“…To know whether A206stop retains the properties of Hv channels, we assessed several hallmark properties of Hv channel currents, including proton permeation, zinc sensitivity, and pHdependent gating (26,27). We initially examined proton-exporting activity by measuring intracellular pH (pH in ) using a pH-sensitive ratiometric dye, BCECF, under whole-cell patch clamp.…”
Section: Resultsmentioning
confidence: 99%
“…We model Hv voltage-dependent gating with a two-state Boltzmann function with midpoint activation voltage V mid = 40 mV and valence 3 5; 15.…”
Section: Understanding the Time Course Of Fluorescence Decaymentioning
confidence: 99%
“…At present, no evidence even suggests that any other ion can permeate. Numerous studies in many cell types have demonstrated that when the dominant cation or anion in the bathing solution is changed, the measured reversal potential ( V rev ) does not change, after liquid junction potentials are corrected (56, 58, 200). Any small deviation of V rev from the Nernst potential for protons ( E H ), is therefore attributable to imperfect control of pH.…”
Section: Introductionmentioning
confidence: 99%